Draft genome of ochrobactrum intermedium strain M86 isolated from non-ulcer dyspeptic individual from India - Kulkarni, Girish; Dhotre, Dhiraj; Dharne, Mahesh S.; Shetty, Sudarshan; Chowdhury, Somak; Misra, Vatsala; Misra, Sriprakash; Patole, Milind; Shouche, Yogesh (GUT Pathogens, 2013)
Background: Ochrobactrum intermedium is an emerging opportunistic pathogen of humans that is closely related to members of the genus Brucella. Earlier, we reported the case of an Indian subject with non-ulcer dyspeptic symptoms whose urease positive gastric biopsy revealed the presence of Helicobacter pylori along with non-Helicobacter like bacteria, eventually cultured and identified as O. intermedium strain M86. Results: Here, we describe the unclosed draft genome of the strain M86 with a length of 5,188,688 bp and mean G+C content of 57.9%. We have also identified many putative gene clusters that might be responsible for its persistence in the gastric mucosa. Comparative analysis of genomic features of Ochrobactrum intermedium strain M86 and Ochrobactrum intermedium LMG 3301(T) was also done. Conclusions: This paper attempts to gain whole-genome based insights into the putative gene determinants of O. intermedium for survival in the highly acidic stomach lumen environment. Identification of genes putatively involved in the various metabolic pathways may lead to a better understanding of the survival of O. intermdedium in acidic condition.